KITA FIT Application: validate through the system usability scale (SUS) - Ramadhan, Dilardi; Sary, Putri Kemuning; Muziffar, Muhammad Fayyadh Rasyid; Ali, Wisnu Taqiudin; Nur, Lutfi; Mustaqim, Ridha (Universitas Suryakancana, 2023)
The accuracy of physical movement in the world of sports and health, as well as the problems arising from a lack of understanding of the basic principles of exercise and the lack of literacy in the digital age, are issues that need to be solved. The research aims to validate, evaluate, and develop the Android-based We Fit App for the community as well as educational learning media for improving sports literacy and physical literacy in the era of digitalization. The research method uses the Likert scale and the System Usability Scale (SUS), involving the public and students. Research results show that our Fit app is successful and can be said to be worthwhile in improving digital literacy and physical literacy in society, with a high level of user satisfaction. Includes features of sports articles, brief insights, learning videos, quizzes, and reading references supporting the development of digital literacy in the world of sports The average user stated that the Kita Fit app's validity score reached 4.7, which indicates that it is worth using and effective when used. Here's a summary of the application draft results from the embroidery that has been made. The Kita Fit team developed the features and contents of the app based on the judgment of the user during the validity test, this strengthens user satisfaction with the use of the application for everyday activities.Key words: literacy, sports literation, digital literature, physical, health, the era of digitalization